Wolbachia-Based Dengue Control Strategy Against Insecticide-Resistant Aedes Aegypti: A Literature Review - Ni Kadek Meta Jayanti; Putu Ayu Asri Damayanti; I Made Sudarmaja (Syntax Corporation, 2026)
Dengue Hemorrhagic Fever (DHF) is a tropical disease associated with dengue virus infection and remains one of the largest vector-borne health problems worldwide. Approximately 390 million cases are caused annually by dengue virus infection, which is transmitted through the bite of the Aedes aegypti mosquito. Therefore, this literature review aims to explore the biomolecular mechanisms underlying the utilization of Wolbachia bacteria, evaluate the potential and effectiveness of this method in dengue vector control, and analyze various challenges and opportunities related to the latest developments in the implementation of Wolbachia-based strategies as a long-term dengue vector control approach. A literature search was conducted using the keywords “Wolbachia,” “Dengue,” “Resistance,” and “Aedes” through PubMed, ScienceDirect, and Scopus, with a focus on studies reporting dengue incidence and mosquito population dynamics. Wolbachia pipientis is an intracellular bacterium capable of inhibiting the replication of arboviruses, including the dengue virus, within the mosquito body by utilizing lipid resources to suppress viral replication and activate the immune system of the Aedes aegypti mosquito. According to research findings from several countries, the implementation of this method has successfully reduced the number of dengue cases and lowered the risk of dengue infection by approximately 40–77%, with sustained reductions observed over longer periods. Economic analyses of this intervention have also demonstrated that the method is cost-efficient, with a cost per Disability-Adjusted Life Year (DALY) of less than USD 1,500 and healthcare savings of up to USD 538,000 per 1,000 population. Overall, the utilization of Wolbachia has proven to be both effective and cost-efficient in reducing dengue fever incidence and controlling mosquito populations.